Influence of culture on psychological gender differences - O. Kh. Aimaganbetova; S. K. Zhantikeyev; E. T. Adilova; Z. М. Sadvakassova; L. Kasym (Хабаршы. Психология және социология сериясы, 2019)
This article is devoted to the study of the influence of culture on psychological gender differences. In defining the very concept of “gender”, we proceeded from the generally accepted understanding that gender is primarily a social and biological characteristic, thanks to which the whole world is divided into the world of men and women. Consequently, in modern cross-cultural psychology, gender is viewed as a complex sociocultural construct that determines differences in roles, behavior, mental and emotional characteristics of men and women.The article presents the basic concepts of gender studies, theories and methods of gender studies in a cross-cultural context, and also studies psychological gender differences in different cultures. Also described are the theoretical and methodological aspects of conducting applied gender studies - D. Matsumoto, J. Berry, G. Triandis, and others, the focus of which is the study of the main attributes of masculinity and femininity. An analysis of the results of these studies allowed J. Berry and his colleagues to conclude that a high degree of agreement on male and female stereotypes proved the effect of psychological universals that determine gender characteristics.Thus, studying the influence of culture on psychological gender differences gave us the opportunity to formulate the conclusion that any type of culture contributes to the manifestation of certain differences in behavior between men and women, as well as differences related to their role, responsibilities and responsibilities in society, what appears to be true for one culture may not be for another. In this regard, we need to further explore the role that culture plays in creating and maintaining gender and gender differences.